Dieselgate: How Hubris and Bad Leadership Caused the Biggest Scandal in Automotive History. (4th July 2019) - Mujkic, Edin; Klingner, Donald
Abstract : The Volkswagen diesel emissions scandal ("Dieselgate") explores how one of the world's largest and most highly-regarded auto manufacturers became ensnared in a self-inflicted and staggeringly costly cheating scandal that reflected poor environmental scanning; inadequate decision-making; unethical corporate leadership; lack of accountability; and inadequate public relations and damage control. It supports the hypothesis that multinational corporations (MNCs) cannot both meet their corporate boards' and stockholders' return on investment (ROI) targets and, by branding themselves as socially responsible enterprises (SREs), produce competitively-priced products that also meet the demands of socially and environmentally conscious consumers. If MNCs cannot be trusted to police themselves as self-branded SREs, and if consumers do not necessarily make choices favoring the socially conscious values they espouse, then government regulations must continue to hold MNCs to appropriate standards of leadership, ethics, and accountability.